A rapid automated protocol for muscle fiber population analysis in rat muscle cross sections using myosin heavy chain immunohistochemistry - Bergmeister, Konstantin D. (JoVE. Video journal, 2017)
Here, we present a protocol for rapid muscle fiber analyses, which allows improved staining quality, and thereby automatic acquisition...